A study on mechanical safety aspects of a riveted joint used in a baby walker / Iskandar Dzulkarnaen Mazlee and Mohamad Nizam Zulkifly - Mazlee, Iskandar Dzulkarnaen; Zulkifly, Mohamad Nizam (2002)
This project report is about understanding the analysis on mechanical safety of baby walker. To do this, a couple of fixtures were designed, fabricated, and tested. From the result of the analysis, we can determine how the baby walker structure and rivet failed. By understanding this concept, the student especially Mechanical Engineering student able to apply it on the other types of joints or structures. To achieve the objective of this project, the students actually have to pass a few steps. Firstly they have to study the theory of baby walker and rivet. This is very important because from this theory the student then will know how to design the fixture, to fabricate and to perform testing successfully.